2021
DOI: 10.3390/ijms22179622
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Resequencing Analyses Provide Insight into Differences in Organic Acid Accumulation in Two Pear Varieties

Abstract: Fruit acidity is one of the main determinants of fruit flavor and a target trait in fruit breeding. However, the genomic mechanisms governing acidity variation among different pear varieties remain poorly understood. In this study, two pear varieties with contrasting organic acid levels, ‘Dangshansuli’ (low-acidity) and ‘Amute’ (high-acidity), were selected, and a combination of transcriptome and population genomics analyses were applied to characterize their patterns of gene expression and genetic variation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Here we also found that the malate contents (2.5 mg/g) are higher than the citrate contents (1.5 mg/g) in the pulp of a ripe pear fruit (Figure 1C). In plants, malate regulation was also widely studied among different species of pear fruit [10,39,40]. For example, cMDH and MS are considered important enzymes to produce malic acid, while mMDH and ME are the key enzymes to degrade malate into oxaloacetate and pyruvate, respectively [11].…”
Section: Discussionmentioning
confidence: 99%
“…Here we also found that the malate contents (2.5 mg/g) are higher than the citrate contents (1.5 mg/g) in the pulp of a ripe pear fruit (Figure 1C). In plants, malate regulation was also widely studied among different species of pear fruit [10,39,40]. For example, cMDH and MS are considered important enzymes to produce malic acid, while mMDH and ME are the key enzymes to degrade malate into oxaloacetate and pyruvate, respectively [11].…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq was conducted for ‘Dangshansuli’ pulp collected from different developmental stages (15, 45, 90, 120 and 145 DAF) with three replicates [ 87 ]. Adapter, ploy-N and low-quality reads were removed from the raw reads to produce clean reads.…”
Section: Methodsmentioning
confidence: 99%